Iot device for monitoring the tilt of containment in basket gabions - Silva, Anderson Bezerra da; Paschoalin Filho, João Alexandre; Ribeiro, Joana Paula Machado (National Journal of City Management, 2024)
In the present work, an IoT (Internet of Things) electronic device was developed, used, and evaluated to monitor and measure the inclination of a containment structure executed in box gabions. This device collected information from an accelerometer, sending it over the internet to a cloud server, where this data was stored, allowing access to the history of the slope variation. The readings collected by the equipment made it possible to correlate its variations to the executive phases of the containment and to conduct statistical analyses to verify whether the variations captured by the sensor consisted of a possible lack of containment.